Cost effective tanker design configurations for reduced oil ouflow - Wong, Jody Jia Qi (2015)
In the recent years, there is a need to relocate resources to cope with the high demand of energy worldwide due to resources being sporadically distributed. The relocation of such resources like that of oil are usually transported via underground pipes, rail or more commonly aboard oil tanker vessels. This paper identifies the cost effectiveness in the various Panamax, Aframax, Suezmax as well as VLCC tanker configurations and its risk controlled probabilistic methods in evaluating the crashworthiness of newly designed tanker configurations using a theoretical risk model based on historical data. The results demonstrate that the option of the increment of side tanks width would provide for the lowest Gross Cost of Averting One Tonne of Oil Spilled.